Assessment of effectiveness of a foot-and-mouth disease vaccine in cattle in Ethiopia - Jemberu, Wudu T.; Molla, W.; Fentie, T.; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2022)
This study was aimed at evaluating the field effectiveness of a trivalent foot and mouth disease (FMD) vaccine (containing serotypes O, A and SAT 2), produced and widely used in Ethiopia, in terms of preventing clinical infection and severe disease. A randomized controlled trial design was employed in the study in which the attack rate of clinical FMD infection in vaccinated cattle was compared with the attack rate in unvaccinated controls in cattle population of 16 villages in Gondar Zuria district, Northwest Ethiopia. The vaccine was administered as a single dose course in the face of an impending FMD outbreak and the trial groups were monitored for clinical infection until the end of the outbreak. The attack rate of clinical FMD in the vaccinated cattle (34%) was significantly lower than the attack rate in unvaccinated controls (49%) (p< 0.001). However, the effectiveness of the vaccine was only 31% (95%CI: 20 - 40%). The proportion of severely affected cattle in the vaccinated group (5.7%) was significantly lower than in the unvaccinated group (9.4%) (p< 0.001), resulting in 39% (95%CI: 18-55%) vaccine effectiveness against severe disease. The observed level of vaccine effectiveness was lower than the internationally recommended 70% expected percentage of protection for a standard potency 3PD50/dose FMD vaccine. Moreover, the level of effectiveness was insufficient to provide herd immunity to control the disease at the population level. Nevertheless, given the significant difference in the incidence of clinical disease between vaccinated and unvaccinated cattle, it might still be cost-effective to use the current vaccine to reduce production losses. Factors that cause low effectiveness of the vaccine need to be identified and addressed for effective control of the disease at population level.